EVALUASI BIOMEKANIKA KERJA DESAIN GEROBAK SAMPAH - Hafizh, Faishal
The activities related to manual waste collecting method in Indonesia – using a two-wheeled cart – could have musculoskeletal disorders or MSDs risks. The waste volume that should be collected manually and the design of the cart were some factors contributed to the risks. The cart design resulted in the worker’s awkward posture while doing the cart-pulling task. Ergonomics approach, Biomechanics in this case, could be used to evaluate the risks in order to find design alternatives if necessary. In this research, the prevalence of musculoskeletal complaints amongst the workers would be evaluated using Nordic Body Map. The risk of MSDs would also be evaluated using REBA. Compression and shear force at L5/S1 of worker’s awkward postures would also be calculated using 3DSSPP simulation. The result of the simulation showed that there were relatively high musculoskeletal complaints at workers’ back and lowback. From the analysis of biomechanical evaluation, the handles used for pulling the waste cart actually had low functionality. Workers actually used ropes, tied to their shoulder to pull the waste cart. Thus, the compression and shear force couldn’t be simulated accurately. The result of the simulation showed that the compression force was actually higher at L4/L5 rather than at L5/S1.